2019
DOI: 10.5530/ijper.54.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Direct Brain Targeted Nanostructured Lipid Carriers for Sustained Release of Schizophrenic Drug: Formulation, Characterization and Pharmacokinetic Studies

Abstract: Background: Systemic drug delivery in schizophrenia is a major challenge, owing to the Blood-brain Barrier (BBB) and P-glycoprotein related effects. Consequently, herein an attempt is made to systemically deliver the most desirable schizophrenia drug, Quetiapine Fumarate (QF) via non-invasive intranasal route using Nanostructured Lipid Carrier (NLC) approach. Materials and Methods: The desired QF loaded NLCs were developed using central composite statistical design and the developed formulations were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The QF blood–brain ratio showed a 10-fold increase for NLCs administered through the nasal route (in comparison to the intravenous route), supporting retention of the drug at the desired site. The study supports a potential nose-to-brain transport of QF-NLC for the effective management of schizophrenia by circumventing the BBB [ 165 ].…”
Section: Lipid-based Nanocarrier Systems For Cns Deliverysupporting
confidence: 70%
“…The QF blood–brain ratio showed a 10-fold increase for NLCs administered through the nasal route (in comparison to the intravenous route), supporting retention of the drug at the desired site. The study supports a potential nose-to-brain transport of QF-NLC for the effective management of schizophrenia by circumventing the BBB [ 165 ].…”
Section: Lipid-based Nanocarrier Systems For Cns Deliverysupporting
confidence: 70%
“…Their innovative approach, involving the modification of nanoparticles with borneol, demonstrated enhanced brain delivery, showcasing the versatility of lipid-based carriers in optimizing intranasal drug delivery. Direct brain-targeted nanostructured lipid carriers for the sustained release of a schizophrenic drug were developed by Sivadasu et al [ 70 ]. The study encompassed formulation development, characterization, and pharmacokinetic evaluations, establishing the potential of lipid-based carriers in sustaining drug release and optimizing therapeutic outcomes for psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated the superiority of the developed quetiapine-loaded NLC formulation as a stable drug-delivery system. Overall, it was concluded that the NLCs provide a promising approach to enhance the transportation of quetiapine to the brain, hence addressing the treatment of bipolar disorder [ 132 ]. The potential of NLCs in delivering diazepam-loaded NLCs by intranasal delivery and the possible toxicity were reported.…”
Section: Nanoparticles For Nose-to-brain Drug Deliverymentioning
confidence: 99%